A formação continuada e o fazer cotidiano da alfabetização nos anos iniciais do Ensino Fundamental em São Mateus/ES, no período de 2013 a 2022 - Faustino, Plenda de Jesus (2023)
Continuing training is an important element in the professional career of teachers, as it contributes to the re/construction and mobilization of knowledge, in addition to enhancing teaching pedagogical practice. The dissertation aimed to understand the ongoing training offered by the municipal network of São Mateus, ES, its implications for the daily lives of literacy teachers and the perceptions of the pedagogical monitoring carried out by the Municipal Department of Education, from 2013 to 2022. The theoretical contributions that supported and enriched the text has the predominance of knowledge, expressions and understandings of teacher training, according to the authors Tardif (2019), Gauthier (2013) and Foerste (2005), as well as the contributions of Souza (2015) in the narratives of professionals and We rely on Soares (2020) with its implications for the literacy process. This is a qualitative research, where the protagonists were the working group composed of 10 literacy teachers, who with their narratives through questionnaires, interviews and reports of experiences enhanced the dialogues about Continuing Education in their personal and professional trajectory. . The results indicated that the continued training provided to teachers in the Literacy Cycle in recent years contributed to changing the daily practice of some teachers in an attitudinal and didactic way. These professionals were formed throughout the training movements based on interactions with other peers and narratives of everyday experiences. Despite all the mobilization of continuing education in the municipal network, it was found that some students finish this school stage, 3rd year, without consolidating all the necessary skills, pointing out that in addition to the participation of teachers in continuing education, this professional needs be impacted by what is offered in them and that the mobilization of the knowledge learned requires time. Furthermore, other elements external to education significantly interfere with the success of student learning.